2015
DOI: 10.5530/pj.2016.1.14
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS Analysis and Potential Cytotoxic Activity of Haplophyllum tuberculatum Essential Oils Against Lung and Liver Cancer Cells

Abstract: Background: Haplophyllum tuberculatum is a plant belongs to family rutacee. It is rich in volatile oils, fixed oils, alkaloids, and furanocoumarins. It is well known for the huge number of folkloric uses in middle east. Objective: The aim of this study is to establish the chemical composition of the essential oils of Libyan H. tuberculatum and to investigate their cytotoxic potentialities.Materials and Methods: The essential oils of the aerial parts and flowers of H. tuberculatum growing in Libya were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The findings also indicated remarkable cytotoxic effects of the oil against the MCF 7 (breast cancer, IC 50 value of 8.91 μg/mL as compared to the 2.4 μg/mL for the doxorubicin) , HEP2, IC 50 value of 7.9 μg/mL) , and HCT116 (IC 50 value of 6.3 μg/mL compared to 1.9 μg/mL for the doxorubicin) cell lines. These finding also corroborated the previous study, which exhibited the cytotoxic potential of the H. tuberculatum oil against the HEPG2 and H1299 35) cells.…”
Section: Cytotoxic Effectssupporting
confidence: 92%
“…The findings also indicated remarkable cytotoxic effects of the oil against the MCF 7 (breast cancer, IC 50 value of 8.91 μg/mL as compared to the 2.4 μg/mL for the doxorubicin) , HEP2, IC 50 value of 7.9 μg/mL) , and HCT116 (IC 50 value of 6.3 μg/mL compared to 1.9 μg/mL for the doxorubicin) cell lines. These finding also corroborated the previous study, which exhibited the cytotoxic potential of the H. tuberculatum oil against the HEPG2 and H1299 35) cells.…”
Section: Cytotoxic Effectssupporting
confidence: 92%
“…While no reports concerning the phytochemical composition and the pharmacological proprieties of the acetonic extract were published for all species of genus Ruta, as the best of the author's acknowledgment. Indeed, most studies of Ruta plants focused mostly on their alkaloid derivatives and essential oil compounds [12,20,22,39], whereas their phenolic contents and pharmacotherapies of them were rarely investigated [17,19,21,40]. That heightened our desire to characterize for the first time the individual phenolic profiles of the EtOAc and acetonic extracts of R. tubercultata aerial parts and to investigate their pharmacological properties.…”
Section: Resultsmentioning
confidence: 99%
“…Studying the chemical composition of essential oil extracted from the Algerian cultivar of S. hortensis L. (Table 1) allows us to know its potential use in various applications such as foods, pharmaceuticals, biopreservation, cosmetics, etc. 12 The extraction process of the present study resulted in a yield of 2.78%, which is higher than that obtained in other Algerian regions like Tizi-Ouzou (0.06%), Bordj-Meńai ̈el (2.2%), and jedioua Relizane (0.68%), as reported by Djenane et al 6,13 Compared to the literature dealing with AHEO reported the present study's findings agree with Djenane et al 6 regarding the volatile profile of ASHEO, with carvacrol, γterpinene, and p-cymene as the predominant compounds. In contrast, Chouitah et al 7 showed a different ASHEO chemotype, where cadinol, thymol, himachalene, and selinene were the major constituents of the volatile fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the chemical composition of essential oil extracted from the Algerian cultivar of S. hortensis L. ( Table 1 ) allows us to know its potential use in various applications such as foods, pharmaceuticals, biopreservation, cosmetics, etc. 12 The extraction process of the present study resulted in a yield of 2.78%, which is higher than that obtained in other Algerian regions like Tizi-Ouzou (0.06%), Bordj-Ménaïel (2.2%), and jedioua Relizane (0.68%), as reported by Djenane et al 6 , 13 and Chouitah et al 7 At the same time, no data are available in the literature about the extraction yield of ASHEO collected from Bou Saada, M’Sila Province in Algeria. Many factors affect the oil yield and the plant’s productivity, such as age, genotype, agronomics, climate, and the harvesting period, Djenane et al 6 …”
Section: Discussionmentioning
confidence: 99%